1997
DOI: 10.1111/j.1439-0442.1997.tb01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenite and Selenium Yeast as Feed Supplements for Dairy Cows

Abstract: Summary The availability of inorganic and organic forms of selenium to dairy cows was studied by giving 25 cows supplementary selenium for 9 months either as sodium selenite or as a selenium‐containing yeast product. Group I (eight cows) received 3.0 mg selenium as sodium selenite daily, group II (nine cows) received 3.0 mg selenium as the selenium yeast product, and group III (eight cows) received 0.75 mg selenium as the selenium yeast product. The total selenium contents of the ration were 0.26–0.32 mg/kg fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 17 publications
7
27
0
1
Order By: Relevance
“…The highly significant differences in selenium concentrations in the liver, striated muscles and myocardium between the control group and the groups receiving organic selenium, as well as between the groups receiving organic and inorganic selenium demonstrate the higher efficacy of organic selenium also in terms of tissue concentrations. Similar results were published by Ortman and Pehrson (1997) as well as Knowles et al (1999) who investigated blood, liver and milk selenium concentrations in cows receiving selenium yeast.…”
Section: Discussionsupporting
confidence: 86%
“…The highly significant differences in selenium concentrations in the liver, striated muscles and myocardium between the control group and the groups receiving organic selenium, as well as between the groups receiving organic and inorganic selenium demonstrate the higher efficacy of organic selenium also in terms of tissue concentrations. Similar results were published by Ortman and Pehrson (1997) as well as Knowles et al (1999) who investigated blood, liver and milk selenium concentrations in cows receiving selenium yeast.…”
Section: Discussionsupporting
confidence: 86%
“…De qualquer maneira, esses estudos têm demonstrado uma maior eficiência de formas orgânicas do Se em aumentar a concentração de Se no sangue e leite de vacas, se comparado às inorgânicas (Tabela 1). Contudo, maior concentração destas formas nas dietas de vacas em lactação de alta produção também implica maiores perdas através da excreção de Se pela glândula mamária, através da caseína e de outras proteínas do leite, que incorporam aleatoriamente SeMet da dieta (MALBE et al, 1995;ORTMAN & PEHRSON, 1997;KNOWLES et al, 1999;MUÑIZ-NAVEIRO et al, 2005). Nesta situação, a proporção que sobra para o animal suprir suas exigências por Se, ou seja, para manter ativas e em normal funcionamento as selenoproteínas funcionais, não é conhecida.…”
Section: Gierusunclassified
“…The main Se supplement that has been used in animal diets is the inorganic form (sodium selenite or selenate). Some studies indicated that organic selenium from selenomethionine (SeMet) or Se enriched yeast is an ideal additive because animals absorb and retain it more than inorganic selenium (Ortman and Pehrson, 1997). Organic selenium is needed not only for healthy and productive animals but also for the production of meat, milk and other products which are rich in selenium (Surai, 2002).…”
Section: Introductionmentioning
confidence: 99%